2022
DOI: 10.3390/molecules27186012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel N-Methylmorpholine-Substituted Benzimidazolium Salts as Potential α-Glucosidase Inhibitors

Abstract: The α-glucosidase enzyme, located in the brush border of the small intestine, is responsible for overall glycemic control in the body. It hydrolyses the 1,4-linkage in the carbohydrates to form blood-absorbable monosaccharides that ultimately increase the blood glucose level. α-Glucosidase inhibitors (AGIs) can reduce hydrolytic activity and help to control type 2 diabetes. Aiming to achieve this, a novel series of 1-benzyl-3-((2-substitutedphenyl)amino)-2-oxoethyl)-2-(morpholinomethyl)-1H-benzimidazol-3-ium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…It is worth noting that the majority of the analogs were found to have good to moderately active IC 50 values ranging from 18.65 ± 0.23 to 28.33 ± 0.02 µM for α-amylase inhibition and with the IC 50 values ranging from 17.47 ± 0.03 to 29.01 ± 0.12 µM for α-glucosidase inhibition except compounds 3a , 3b , and 3h . The inhibitory activities of α-amylase and α-glucosidase, according to Table 3 , revealed that the tested compounds in the current study demonstrate higher activities than those reported in previous studies [ 47 , 72 ].…”
Section: Resultscontrasting
confidence: 46%
“…It is worth noting that the majority of the analogs were found to have good to moderately active IC 50 values ranging from 18.65 ± 0.23 to 28.33 ± 0.02 µM for α-amylase inhibition and with the IC 50 values ranging from 17.47 ± 0.03 to 29.01 ± 0.12 µM for α-glucosidase inhibition except compounds 3a , 3b , and 3h . The inhibitory activities of α-amylase and α-glucosidase, according to Table 3 , revealed that the tested compounds in the current study demonstrate higher activities than those reported in previous studies [ 47 , 72 ].…”
Section: Resultscontrasting
confidence: 46%
“…The most effective inhibitors inhibited the enzyme by 63% and 99%; moreover, these compounds showed antioxidant activity [17]. Khan et al [18] also synthesized a series of 1-benzyl-3-((2-substitutedphenyl)amino)-2-oxoethyl)-2-(morpholinomethyl)-1H-benzimidazol-3-ium chloride (Figure 7) and checked them for α-glucosidase inhibitory activity in vitro. The compound 1-benzyl-3-( 2…”
Section: Morpholine Derivatives As Antidiabetic Drugsmentioning
confidence: 99%
“…The series of 4-(5-fluoro-2-substituted-1H-benzimidazol-6-yl)morpholine derivatives showed remarkable α-glucosidase inhibitory potentials [19]. A compound shown in Figure 8, which has a methoxy group on the phenyl ring, was found to be the most active Khan et al [18] also synthesized a series of 1-benzyl-3-((2-substitutedphenyl)amino)-2oxoethyl)-2-(morpholinomethyl)-1H-benzimidazol-3-ium chloride (Figure 7) and checked them for α-glucosidase inhibitory activity in vitro. The compound 1-benzyl-3-( 2…”
Section: Morpholine Derivatives As Antidiabetic Drugsmentioning
confidence: 99%
“…The coupling of two or more pharmacologically important scaffolds is a diverse approach that can produce hybrid molecules with enhanced biological activity. In continuation of our previous research work dealing with the development of various enzyme inhibitors, for example, α-amylase and α-glucosidase inhibitors ( Khan et al, 2021 ; Khan et al, 2022 ; Saddique et al, 2022 ), we herein report a novel series of pyridine-based piperazines as potent urease inhibitors.…”
Section: Introductionmentioning
confidence: 99%